Relationship Of Early Complementary Food And Diarrhea In Infants Aged 0-6 Months In Posyandu Sedap Night Tengger East Kandangan Surabaya - Novianti, Hinda; Khairunnisa, Khairunnisa (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Giving complementary foods too early will result in the baby’s digestive ability not ready to receive additional food. This will have an impact such as diarrhea. The design in this study was cross sectional. The population were 50 mothers who had babies aged 0-6 months. The sample were 45 people was taken using simple random sampling. Data analysis using test Chi-square. The results was almost all respondents (91.1%) gave early complementary breastfeeding. And 41 respondents who provided early complementary breastfeeding, most of them had diarrhea (68.3%). Based on the statistical test, the significance value of α = 0.05 obtained p-value = 0.016, which means that the p-value <α, then H0 is rejected, meaning that there is a relationship between early complementary breastfeeding and the incidence of diarrhea. Thus, it is hoped that health services will provide more health education to the community.